Participatory parity in schooling and moves towards ordinariness: a comparison of refugee education policy and practice in England and Sweden - McIntyre, Joanna; Neuhaus, Sinikka; Blennow, Katarina (Taylor & Francis, 2018)
Within the current global refugee crisis this paper emphasises the fundamental role of education in facilitating the integration of young new arrivals. It argues that a humanitarian crisis of such scale requires a commensurate humanitarian response in the form of socially-just educational policies and practices in resettlement contexts within Europe. Utilising the theoretical concepts of Fraser’s ‘participatory parity’ and Kohli’s ‘resumption of an ordinary life’ we explore educational policy making in Sweden and England, noting how the framing of these policies indicates how different nation states view their role in the global migration crisis. In England, child refugees are rendered invisible and not a legitimate focus of national educational policy whereas in Sweden they are foregrounded in policy discourse though not necessarily in policy enactment. The paper concludes that newly arrived future citizens of Europe require socially-just policy and practice to best serve their and their resettlement context’s best interests.